2005
DOI: 10.14356/kona.2005012
|View full text |Cite
|
Sign up to set email alerts
|

Aerogels: Tailor-made Carriers for Immediate and Prolonged Drug Release

Abstract: The potential of inorganic polymeric materials Ҁ silica aerogels Ҁ as tailor - In addition, the possibility of generating organic microparticles inside the pores of the aerogels by precipitation from supercritical solutions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 29 publications
0
32
1
1
Order By: Relevance
“…Smirnova et al [54] reported the possibility of controlling the dissolution rate of poorly soluble drugs by adsorption on silica aerogels with various properties. The drug concentration in aerogel is determined by the working temperature, bulk concentration of the drug in the supercritical solvent and the properties of the aerogel.…”
Section: Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smirnova et al [54] reported the possibility of controlling the dissolution rate of poorly soluble drugs by adsorption on silica aerogels with various properties. The drug concentration in aerogel is determined by the working temperature, bulk concentration of the drug in the supercritical solvent and the properties of the aerogel.…”
Section: Aerogelsmentioning
confidence: 99%
“…For a given drug, the loading increases with increasing surface area and volume of the mesopores of the aerogel, whereas hydrophilic samples have higher loading rates than hydrophobic ones in all cases. The authors showed that hydrophobic aerogels exhibited a slower release rate of drugs which is governed by diffusion, since such aerogels are more stable in water [54]. This property may prove useful for the prolonged release of fast dissolving drugs.…”
Section: Aerogelsmentioning
confidence: 99%
“…Therefore, the structural properties of aerogels such as density, pore size, and surface area and the functionality of the surface influence the adsorption process and thus the maximum loading as well. For a given drug, the loading increases with increasing surface area and with the volume of the mesopores of the aerogel [10,11]. Usually, higher density aerogels, having larger surface areas, adsorb more drugs than samples of lower density [7].…”
Section: Loading Of Aerogels By Adsorptionmentioning
confidence: 99%
“…Although in reality more complex behaviour is expected, this fitting gives a first idea about the release rate: the release rate of ketoprofen from hydrophilic aerogel is five times higher than that of the crystalline drug. In case of another drug, griseofulvin, the release from silica aerogels was compared to that of the dissolution of griseofulvin micro-and nanoparticles [11]. As can be seen from Figure 31.5, the release rate increases with decreasing particle size and is by far the highest in case of the powdered aerogel formulation.…”
Section: Release Of the Drugs From Silica Aerogelsmentioning
confidence: 99%
“…These unique properties of aerogels attracted many researchers to explore them as drug delivery vehicles [1]- [5].…”
Section: Introductionmentioning
confidence: 99%